2019
DOI: 10.1093/nar/gkz470
|View full text |Cite
|
Sign up to set email alerts
|

Structures and mechanism of transcription initiation by bacterial ECF factors

Abstract: Bacterial RNA polymerase (RNAP) forms distinct holoenzymes with extra-cytoplasmic function (ECF) σ factors to initiate specific gene expression programs. In this study, we report a cryo-EM structure at 4.0 Å of Escherichia coli transcription initiation complex comprising σE—the most-studied bacterial ECF σ factor (Ec σE-RPo), and a crystal structure at 3.1 Å of Mycobacterium tuberculosis transcription initiation complex with a chimeric σH/E (Mtb σH/E-RPo). The structure of Ec σE-RPo reveals key interactions es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 67 publications
(80 reference statements)
4
51
1
Order By: Relevance
“…We calculated the MI between all positions in the promoter and protein alignments and found that only a few amino acids -nucleotide positions had high MI ( Figure 1B). High MI amino acid -nucleotide interactions were consistent with specificity determining interactions observed in the structures of 3 divergent ECF σ s bound to their cognate promoters: E. coli RpoE and Mycobacterium tuberculosis SigH and SigL (Lane and Darst 2006;Campagne et al 2014;Lin et al 2019;Fang et al 2019;Li et al 2019; Figure 1B). Taken together, these data suggest that the mechanism of ECF σ -promoter interaction is conserved in a majority of ECF σ s despite their extensive sequence divergence, implying that our collection of matching ECF σ s and putative promoters can serve as a dictionary in which the promoter specificity conferred by any amino acid at key DNA recognizing positions can be determined.…”
Section: Ecf σ S Interact With Dna In a Conserved Fashionsupporting
confidence: 77%
See 2 more Smart Citations
“…We calculated the MI between all positions in the promoter and protein alignments and found that only a few amino acids -nucleotide positions had high MI ( Figure 1B). High MI amino acid -nucleotide interactions were consistent with specificity determining interactions observed in the structures of 3 divergent ECF σ s bound to their cognate promoters: E. coli RpoE and Mycobacterium tuberculosis SigH and SigL (Lane and Darst 2006;Campagne et al 2014;Lin et al 2019;Fang et al 2019;Li et al 2019; Figure 1B). Taken together, these data suggest that the mechanism of ECF σ -promoter interaction is conserved in a majority of ECF σ s despite their extensive sequence divergence, implying that our collection of matching ECF σ s and putative promoters can serve as a dictionary in which the promoter specificity conferred by any amino acid at key DNA recognizing positions can be determined.…”
Section: Ecf σ S Interact With Dna In a Conserved Fashionsupporting
confidence: 77%
“…Since the amino acid at Arg173 RpoE is not positioned to make base-specific interactions, this is likely due to a role in positioning the amino acid at Finally, we tested the effect of amino acid substitutions at the Asn84 RpoE position of ECF11_987 on -12 and -13 nucleotide specificity ( Supplementary Table 3). Whereas all previously solved DNA-bound ECF σ structures reported that the amino acid at the Asn84 RpoE position makes a hydrogen bond with the -12 base of the promoter (Campagne et al 2014;Lin et al 2019;Fang et al 2019;Li et al 2019), our MI analysis suggested that the Asn84 RpoE identity determines both -12 and -13 nucleotide specificity. We therefore tested the ability of all Asn84 RpoE substitutions of ECF11_987 to drive transcription from 16 variants of the ECF11_987 promoter modified at the -13 and/or -12 nucleotide positions (Methods).…”
Section: The Identify Of Key Amino Acid Positions Determines Promotercontrasting
confidence: 74%
See 1 more Smart Citation
“…2E). We interpret the successive changes in [6][7][8]. As a first step to assess whether the difference in s-finger length and sequence for ECF s factors vs. primary s factors affects the mechanism of initiation-factor displacement, we have performed an analysis analogous to that in Fig.…”
Section: Rnamentioning
confidence: 99%
“…S4A-B) Stepwise, RNA-driven displacement of the s finger: ECF s factor s L The s fingers of different ECF s factors vary in length and sequence (ref. 6). As a second step to assess whether the difference in s-finger length and sequence for ECF s factors vs. primary s factors affects the mechanism of initiation-factor displacement, we have performed an analysis analogous to that in Fig.…”
Section: In the Crystal Structures Ofmentioning
confidence: 99%